Reverse Phase HPLC Profiling of Antioxidant and Antimicrobial Activities of Sarcochlamys pulcherrima (Roxb.) Gaud. (International Current Pharmaceutical Journal, 2016)
The total phenolics content, total flavonoids content, antioxidant activity and antimicrobial activity of methanol extract and its derived fractions from Sarcochlamys pulcherrima (Roxb.) Gaud. were evaluated. The plant material was initially extracted with methanol. The fractionation was carried out using liquid-liquid extraction with hexane, ethyl acetate, n-butanol, and water. The Folin-Ciocalteu assay was used to quantify total phenolics content, Aluminum Chloride assay to quantify total flavonoids content, DPPH (2, 2-diphenyl-1-picrylhydrazine) and reducing power assay are to determine antioxidant activity. The ethyl acetate fraction was observed to contain high phenolic content (201.37 mg/g) followed by n-butanol fraction (197.76 mg/g), methanol extract (136.93mg), water fraction (55.05mg/g) and hexane fraction (36.94mg/g) respectively. The flavonoids content ranges from 109.48 mg/g to 8.63 mg/g dry extract. The highest antioxidant activity was found in n-butanol fraction (EC50 =14.69 µg/mL in DPPH and 162.65 µg/mL in reducing power). The antimicrobial activity of the samples was evaluated based on inhibition zone using agar-well diffusion assay and minimal inhibition concentration (MIC) values. Hexane fraction had no antimicrobial effect against test microorganisms. The zone of inhibitions ranged from 11 mm to 6 mm. The n-butanol fraction possessed the highest antimicrobial activity against E. coli among the four fractions with MIC value of 0.781mg/mL. In addition rutin, gallic acid, quercetin and kaempferol were quantified by reverse phase high performance liquid chromatography (HPLC) method. In ethyl acetate and n-butanol fraction, observed large amount rutin (77.53 ± 7.57 mg/g; 77.45 ± 1.71 mg/g) and gallic acid (61.01 ± 2.34 mg/g; 22.75 ± 1.54 mg/g) as compared to the quercetin and kaempferol.Doley et al., International Current Pharmaceutical Journal, May 2016, 5(6): 49-54